Retained Surgical Drains in Orthopedics: Two Case Reports and a Review of the Literature - John S. Cox; Darin Friess (Case Reports in Orthopedics)
Though a relatively rare event, retained surgical drains are preventable and can lead to significant consequences. Two case reports from our institution are discussed as examples for the challenging management of this problem as well as an overview of techniques for the prevention and removal of retained drains based on the current literature.